Treating the complete denture patient - Golden, William Glen, 1947-; Driscoll, Carl F. (Hoboken, NJ : Wiley-Blackwell, 2020)
'This book presents step-by-step procedures for all techniques, materials, and methods associated with the use of complete dentures in dental practice. Written for dental students, dental general practitioners, and laboratory technicians, the book provides a practical approach to the complete denture patient. More than 800 photographs illustrate the text, making it easy to follow and apply in the practice or laboratory. Treating the Complete Denture Patient covers all topics related to complete dentures, from the initial appointment and impressions to insertion and troubleshooting. Chapters discuss the diagnostic appointment, covering the analyzing of and treatment planning for edentulous patients; the making of preliminary impressions for the beginning stages of treatment; custom trays for final impression appointments; and much more. Treating the Complete Denture Patient is an essential resource for dental general practitioners, dental students, and laboratory technicians Presents easy-to-use, clinically relevant information on all topics related to complete dentures. Covers all the steps associated with providing complete dentures, from the initial appointment and impressions to inserting and troubleshooting problems. Features hundreds of high-quality color photographs to depict the concepts discussed. Includes access to a companion website offering video clips'--
The diagnostic appointment -- Preliminary impressions -- Custom trays : the key to a great final impression -- Using custom trays to make final impressions -- Boxing and pouring a finalfinal impression -- Baseplates and occlusion rims -- Adjusting wax rims to fit the patient -- Using the Denar facebow -- Mounting maxillary casts on the articulator -- Centric relation records -- Selecting proper denture -- Setting anterior denture teeth -- Setting posterior anatomic teeth in bilaterally balanced occlusion -- Setting 0-degree posterior teeth in monoplane occlusion -- Overview of lingualized occlusion -- Setting teeth in a lingualized occlusion -- Adjusting dentures set in lingualized occlusion to fit the patient -- The anterior aesthetic wax try-in -- The complete denture wax-up -- Sealing complete dentures to the cast -- The wax try-in of teeth -- Making an arbitrary posterior palatal seal in the lab -- Interacting with dental labs -- Flasking, packing and processing complete dentures -- Completing a laboratory remount -- Making a remount index -- Remove CD from the cast and finish -- Quality standards in appearance -- Inserting complete dentures in the mouth -- Performing a clinical remount -- Equilibrating dentures set in lingualized occlusion -- Equilibrating fully anatomic (30o) set-ups -- Equilibrating complete dentures set in a monoplane occlusion -- Troubleshooting complete denture problems -- Replacing teeth on a complete denture -- Repairing a broken complete denture -- Using implants to stabilize a CD -- Immediate complete dentures -- Tissue conditioners -- The fabrication of digital complete dentures.
Includes bibliographical references and index.
Keywords: Denture, Complete